Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan dengan Employee Engagement Sebagai Variabel Mediasi (Studi Kasus Pada Lembaga Pendidikan dan Pelatihan Kepolisian Negara Republik Indonesia) - Hafni Ratna Indah; Aryana Satrya; Etty Puji Lestari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The National Police Education and Training Institute is a supporting element in the Indonesian National Police whose task is to plan, develop and carry out educational functions in the context of “Creating Tribrata Persons who are moral, professional, modern and superior”. This study aims to determine the effect of organizational culture and work motivation on employee performance with employee engagement as a mediating variable at the Indonesian National Police Education and Training Institute. The population in this study were all personnel of the National Police Education and Training Center and a sample of 202 people was obtained using the slovin formula. Data was collected using a online questionnaire. The data that has been collected is analyzed by path analysis using PLS. The results of data analysis show that: (1) Organizational culture variable has a direct and significant influence on employee performance, (2) Work motivation variable has a direct and significant influence on employee performance, (3) Organizational culture variable has a direct but not significant effect on employee engagement, (4) Variables of work motivation have a direct and significant influence on employee engagement (5) Variables of organizational culture and work motivation have an indirect influence on employee performance with employee engagement as a mediating variable at the National Police Education and Training Institute (6) Variables of employee engagement have an influence on employee performance